White Blood Cell Count and Neutrophil-Lymphocyte Ratio in Children with Complicated and Uncomplicated Pneumonia - Setyoningrum, Retno Asih; Lestari, Sally Rizkita; Sari, Ratih Kumala; Visuddho, Visuddho; Hapsari, Rika; Chafid, Arda Pratama Putra (Penerbit Goodwood, 2024)
Purpose: Community-acquired pneumonia (CAP) remains one of the leading causes of morbidity and mortality among children, particularly those under the age of five. This study aimed to compare white blood cell (WBC) count and neutrophil-lymphocyte ratio (NLR) between children with complicated and uncomplicated pneumonia hospitalized at Dr. Soetomo Hospital Surabaya. Research methodology: This retrospective study evaluated 49 children hospitalized with CAP from January to October 2021. Pneumonia was diagnosed based on symptoms (fever, cough, dyspnea) and physical findings (tachypnea, chest indrawing, rales). The comparison of WBC count and NLR of children with and without pneumonia complications was made using the Mann-Whitney U test. Results: Of the 49 patients, 28 (57.1%) were male and 40 (81.6%) were under five years old. The median hospital stay was 7 (Interquartile Range [IQR] 4.5 – 9) days. Nine patients (18.4%) had complications, including pneumothorax (33%) and sepsis (22%). Patients with complications had higher median WBC counts (19.5 [IQR 7.2 – 25.1] vs. 12.7 [IQR 10.7 – 15.7] x103/mm3, p=0.224). Similarly, the median NLR was found higher in the complicated pneumonia group (2.9 [IQR 1.5 – 10.8]) than uncomplicated group (1.7 [IQR 0.9 – 4.4], p=0.178). Limitations: The few sample size and retrospective nature of the study limits the generalizability of the findings. Future studies with larger sample sizes and the inclusion of additional biomarkers are warranted to confirm our findings. Contribution: These trends suggest potential utility of WBC count and NLR as biomarkers for pneumonia severity, warranting further research with larger cohorts.